2017
DOI: 10.3126/jcmc.v7i1.17363
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of vitamin D deficiency/insufficiency among children and adolescents

Abstract: Background: Vitamin D is an essential prohormone for the normal skeletal and extraskeletal health. Vitamin D deficiency/ insufficiency is an unrecognized epidemic among children and adults worldwide. There are growing data from studies of young children and adolescents in other countries, but a limited information are available regarding the prevalence of this nutritional deficiency/insufficiency among the Nepalese children and adolescents. Thus this study was aimed to find out the prevalence of vitamin D defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…32 In our study, the overall prevalence rates of vitamin D insufficiency and deficiency were 35.9% and 34.8% respectively. In the study by Regmi et al, 20 17.6% of the study subjects were insufficient; 56.5% were deficient; and 27.8% were severely deficient (levels <10ng/mL) in vitamin D. The study population in that study were children and youngsters, i.e., the age-group comparable to the first quartile of age in our study. We found in our study that patients in the first and second quartiles of age demonstrated greater proportions of deficiency, whereas those in the third and last quartiles showed greater proportions of insufficiency.…”
Section: Resultsmentioning
confidence: 45%
See 3 more Smart Citations
“…32 In our study, the overall prevalence rates of vitamin D insufficiency and deficiency were 35.9% and 34.8% respectively. In the study by Regmi et al, 20 17.6% of the study subjects were insufficient; 56.5% were deficient; and 27.8% were severely deficient (levels <10ng/mL) in vitamin D. The study population in that study were children and youngsters, i.e., the age-group comparable to the first quartile of age in our study. We found in our study that patients in the first and second quartiles of age demonstrated greater proportions of deficiency, whereas those in the third and last quartiles showed greater proportions of insufficiency.…”
Section: Resultsmentioning
confidence: 45%
“…Bhatta et al 18 , found the prevalence of hypovitaminosis D to be 75.4% in females and 70.1% in males. Regmi et al 20 reported a higher prevalence of hypovitaminosis D in females (children and youngsters) (80.9%) as compared to males (68.9%) of same age-group. Although the authors didn't report any statistical inference, the difference in proportion (i.e., 12.0%) was in contrast to our finding, especially in the first quartile of age.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Regmi et al have reported 74.1% vitamin D deficiency in a hospital-based study from Nepal. 1 Around 90% of apparently healthy Indians have subnormal vitamin D levels. 2 Vitamin D deficiency is reported in many populations across the world regardless of age and gender.…”
Section: Introductionmentioning
confidence: 99%